Association between four-dimensional echocardiographic left atrial measures and left atrial fibrosis assessed by left atrial late gadolinium enhancement. (29th December 2021) - Olsen, Flemming Javier; Bertelsen, Litten; Vejlstrup, Niels; Diederichsen, Søren Zöga; Bjerregaard, Caroline Løkke; Graff, Claus; Brandes, Axel; Krieger, Derk; Haugan, Ketil; Køber, Lars; Højberg, Søren; Svendsen, Jesper Hastrup; et al.
Abstract: Aims: Left atrial (LA) fibrosis is a hallmark of atrial cardiomyopathy, and non-invasive surrogate measures of LA fibrosis are therefore needed. We investigated the association between four-dimensional (4D) echocardiographic LA measures and LA fibrosis. Methods and results: A multimodality imaging substudy was performed in a randomized clinical trial (LOOP study), recruiting elderly participants with cardiovascular risk factors. LA late gadolinium enhancement (LGE) by cardiac magnetic resonance imaging was used as a surrogate for LA fibrosis. 4D echocardiographic LA quantification was used to measure maximal and minimal LA volume (LAVmax and LAVmin, respectively), LA emptying fractions (LAEFtotal ), and strain. Logistic regression was used to relate LA measures to high LA LGE (≥17 cm 2 ). Of the 44 participants (mean age 76 years, 64% men, median LA LGE 13.1 cm 2 ), 14 exhibited high LA LGE. These participants exhibited abnormalities in several LA functional measures but not LAVmax . In linear regressions, only increasing LAVmin, and decreasing LAEFtotal, and reservoir strain were associated with increasing LA LGE. Furthermore, increasing LAVmin was associated with a higher likelihood of high LA LGE [odds ratio (OR) = 1.19 (1.04–1.37)]. Decreasing LAEFtotal and reservoir strain were also associated with higher likelihood of LA LGE [OR = 1.18 (1.05–1.33)] and OR = 1.15 (1.02–1.30), per 1% decrease in LAEFtotal and reservoir strain, respectively]. These findings were consistent after multivariable adjustments. LAEFtotal provided the highest performance for detecting high LA LGE (area under the curve of 0.78). Conclusion: LAVmin, LAEFtotal, and reservoir strain measured by 4D echocardiography are significantly associated with LA LGE. LAEFtotal provides the best performance for detecting high LA LGE. Graphical Abstract: